The prodigal daughter - Archer, Jeffrey, 1940-; King, Lorelei (New York, NY : Hodder and Stoughton : Audio Renaissance, Coronet Books, 1982)
Florentyna Kane inherited from her immigrant father a vast hotel empire and a love for America. She finds fulfillment in love and family along the path to power, moving just a heartbeat away from her ultimate goal-- becoming the first female president of the United States. But she discovers that the price of power may be more than she is willing to pay.
Abridged.
Originally published in 1982.
Compact disc.
Read by Lorelei King.
Keywords: Businesswomen -- Fiction; Capitalists and financiers -- Illinois -- Chicago -- Fiction; Presidential candidates -- United States -- Fiction; Women -- Political activity -- United States -- Fiction